Characterization of the denaturation of human alpha-lactalbumin in urea by molecular dynamics simulations. - Smith, L; Jones, R; van Gunsteren, W (2005)
Molecular dynamics (MD) simulations were used to characterize the non-cooperative denaturation of the molten globule A-state of human alpha-lactalbumin by urea. A solvent of explicit urea and water molecules was used, corresponding to a urea concentration of approximately 6M. Three simulations were performed at temperatures of 293K, 360K and 400K, with lengths of 2 ns, 8 ns and 8 ns respectively. The results of the simulations were compared with experimental data from NMR studies of human alpha-lactalbumin and related peptides. During the simulations, hydrogen bonds were formed from the protein to both urea and water molecules as intra-protein hydrogen bonds were lost. Urea was shown to compete efficiently with water as both a hydrogen bond donor and acceptor. Radial distribution functions of water and urea around hydrophobic side chain atoms showed a significant increase in urea molecules in the solvation shell as the side chains became exposed during denaturation. A considerable portion of the native-like secondary structure persisted throughout the simulations. However, in the simulations at 360K and 400K, there were substantial changes in the packing of aromatic and other hydrophobic side chains in the protein, and many native contacts were lost. The results suggest that during the non-cooperative denaturation of the molten globule, secondary structure elements are stabilized by non-specific, non-native interactions.